THE DEVELOPMENT OF HUMAN RESOURCE MANAGEMENT ADVENTAGE STRATEGY FOLLOW TO QUALITY ASSURANCE STANDARD OF RAJAMONGALA UNIVERSITY OF TECHNOLOGY - นิ่มจิตต์ สุรมงคล; จันทึก ธีระวัฒน์ (RMUTT Global Business and Economics Review, 2016)
The objectives of this research were to 1) examine the composition of quality assurance standard’s advantaged human resource management model; 2) develop quality assurance standard’s advantaged human resource management strategic plan and 3) provide quality assurance standard’s advantaged human resource management strategic plan of 9 RMUT campuses. The research method consists of 3 parts. Part 1 involves with the secondary sources by revising information in order to examine major and minor composition of quality assurance standard’s advantaged human resource management strategic plan. It revealed that the major composition includes input factors, process, output, network and creation and innovation also minor composition includes SWOT analysis, vision, mission, goal, human resource selection, staff training and developing, evaluation, compensation and reward, human relation management. Part 2 engages with the future research using EDFR which is a research tool to develop quality assurance standard’s advantaged human resource management strategic plan of RMUT by interviewing 24 respondents. Result showed the model of appropriated quality assurance standard’s advantaged human resource management strategic plan which includes university strategy and quality assurance standard’s input factors, guide for human resource approach, concrete networking building, promotes creative thinking through research and inspiration. Part 3 concerns with the management’s evaluation from 9 RMUT campuses with the Cohen’s Kappa coefficient. It revealed that the development of quality assurance standard’s advantaged human resource management strategic plan was appropriate to employ at 9 RMUT campuses.